A cognitive semantic approach to Costa Rican school-aged children´s lexicon - Díaz Muñoz, Isabel (2023)
The present article encompasses some of the more prominent qualitative results of the dissertation “Categorización y relaciones de inclusión en escolares costarricenses”, which was developed for the authoress to obtain a Master Degree in Linguistics from the University of Costa Rica. From a cognitive semantic approach, it describes data that reveal the distinction between semantic and conceptual structure; at the same time, it accounts for the great creativity and productivity of child lexicon, as well as some social and cultural aspects that affect the way school aged children construct categories and establish semantic relationships.